Sosialisasi Dan Focus Group Discussion (FGD) Balita Stunting Dengan Kader Pendamping Di Desa Mekarsari, Bogor - Rilla Sovitriana; Rimi Gusliana Mais (AMMA : Jurnal Pengabdian Masyarakat, 2023)
In Bogor Regency, stunting cases have decreased in 2021 to 9.89% with a target of 2023, Bogor Regency is Stunting Free. However, in Mekarsari Village there were still 27 stunted children. Mekarsari village has a population of 6,392 people with a maximum education level of high school. In 2021 there are 1,713 people who have not found work, causing low awareness of health and the family economy. This results in inadequate family nutrition and stunting in children. In this community service, activities were carried out with assisting cadre mothers using the Focus Group Discussion (FGD) method and socialization by providing education about stunting toddlers. The implementation of this community service activity aims to further increase the knowledge of the Facilitating Cadres about toddler stunting in the village of Mekarsari, Bogor. Socialization and Focus Group Discussion (FGD) Activities for Stunting Toddlers with Assisting Cadres in Mekarsari Rancabungur Village Village, Bogor went well from the permitting stage to implementation and reporting. The interactive and cooperative response and enthusiasm of the FGD participants is an indicator of successful implementation.